Altering chromatic aberration: how this latest trend in intraocular-lens design affects visual quality in pseudophakic patients - Łabuz, Grzegorz; Güngör, Helin; Auffarth, Gerd U.; Yildirim, Timur Mert; Khoramnia, Ramin (Eye and Vision, 2023)
Chromatic aberration of the eye results from the dispersion of polychromatic light at the interfaces of ocular media. An intraocular lens (IOL) based approach utilizing the diffractive-multifocal principle has been proposed for its correction, but the clinical evidence on the impact of reducing or increasing chromatic aberration on the visual quality of pseudophakic patients remains scarce.
Gesehen am 12.02.2024